2006
DOI: 10.1002/mrm.20793
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the intracellular localization of a Gd‐based imaging probe on the relaxation enhancement of water protons

Abstract: Gd-HPDO3A has been internalized into rat hepatocarcinoma cells in the cytoplasm (by electroporation) or in intracellular vesicles (by pinocytosis), respectively. In the former case, the observed relaxation rates are likely dependent upon the amount of internalized paramagnetic complex, whereas in the latter case the relaxation enhancement is "quenched" to a plateau value (about 3 s ؊1 ) when the entrapped amount of Gd-chelate is higher than 1 ؋ 10 10 Gd/cell. The observed behavior has been accounted in terms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
180
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(195 citation statements)
references
References 22 publications
15
180
0
Order By: Relevance
“…For instance, CA diffuses in cytoplasm after electroporation, and in perinuclear vesicles after pinocytosis. 24 Also, as recently pointed out, differential in vivo stability of commercial Gd chelates is another variable to be take into consideration for longer term studies, 40 but should have no role to play in the relative acute process we had been monitoring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, CA diffuses in cytoplasm after electroporation, and in perinuclear vesicles after pinocytosis. 24 Also, as recently pointed out, differential in vivo stability of commercial Gd chelates is another variable to be take into consideration for longer term studies, 40 but should have no role to play in the relative acute process we had been monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…20,23,24 Grafted on Matrigel structures and subcutaneously implanted, endothelial progenitor cells labeled with Gd-HPDO3A were identified as hyperintensities 14 days after injection. 20 Plugged in mouse kidney, they were visible 24 h after injection.…”
Section: Introductionmentioning
confidence: 99%
“…A third disadvantage of endocytic cell labelling is that the vast majority of the contrast agents are trafficked to the endolysosomes where they are exposed to an acidic and overall degrading environment 26,28 . This can lead to degradation of the contrast agent, lowering the signal intensity, as reported for fluorescent labels [28][29][30] as well as MRI contrast agents [31][32][33] . In addition, it has been reported that nanomaterials trapped in endolysosomal vesicles are not distributed equally over daughter cells upon cell division 30,34,35 .…”
Section: Introductionmentioning
confidence: 99%
“…34,35 Gadolinium internalised via this route is known to localise to endosomes within the perinuclear region of the cell, 34 where subsequent detachment of Gd 3+ from its chelate may occur. 35 Dechelation is expected to be more prevalent for Omniscan than Dotarem.…”
Section: Resultsmentioning
confidence: 99%